Enhancing Fatty Acid Catabolism of Macrophages Within Aberrant Breast Cancer Tumor Microenvironment Can Re-establish Antitumor Function - Gu, Yucui; Niu, Xingjian; Yin, Lei; Wang, Yiran; Yang, Yue; Yang, Xudong; Zhang, Qingyuan; Ji, Hongfei (Frontiers in Cell and Developmental Biology, 2021)
Triple-negative breast cancer (TNBC) remains an intractable challenge owing to its aggressive nature and lack of any known therapeutic targets. Macrophages play a crucial role in cancer promotion and poor prognosis within the tumor microenvironment (TME). The phagocytosis checkpoint in macrophages has broader implications for current cancer immunotherapeutic strategies. Here, we demonstrate the modulation in the antitumor activity of macrophages within the aberrant metabolic microenvironment of TNBC by metabolic intervention. The co-culture of macrophages with TNBC cell lines led to a decrease in both their phagocytic function and expression of interleukin (IL)-1β and inducible nitric oxide synthase (iNOS). The transcription of glycolysis and fatty acid (FA) catabolism-related factors was inhibited within the dysregulated tumor metabolic microenvironment. Enhancement of FA catabolism by treatment with the peroxisome proliferator-activated receptor-alpha (PPAR-α) agonist, fenofibrate (FF), could re-establish macrophages to gain their antineoplastic activity by activating the signal transducer and activator of transcription 1 (STAT1) signaling pathway and increasing ATP production by FA oxidation. The combination of fenofibrate and anti-CD47 therapy significantly inhibited tumor growth in a 4T1 tumor-bearing mouse model. In conclusion, the enhancement of FA catabolism of macrophages could re-establish them to resume antitumor activity in the TME. Anti-CD47 therapy combined with fenofibrate may serve as a novel and potential immunotherapeutic approach for the treatment of TNBC.